Duration of DAPT with N‐DES. Issue 11 (November 2016) - Bello, Jennifer K.
Abstract : N/A: Bittl JA, Baber U, Bradley SM, et al. Duration of dual antiplatelet therapy: a systematic review for the 2016 ACC/AHA guideline focused Update on Duration of Dual Antiplatelet Therapy in Patients With Coronary Artery Disease: a report of the American College of Cardiology/American Heart Association Task Force on Clinical Practice Guidelines. J Am Coll Cardiol . 2016; 68(10):1116–1139.